PENANGANAN SEKULARISASI DALAM LAYANAN BIMBINGAN DAN KONSELING MELALUI INTEGRASI KURIKULUM BERBASIS NILAI ISLAM - Johan, Budi; Yusrofil, Muhammad; Maghfiraldi, Faiz; Ariiq, Farhan; Athoillah, Muhammad Kemal Nurfauzan (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Guidance and counseling (GC) services in schools are still largely dominated by secular modern psychology approaches, which tend to neglect the spiritual dimension of students. This condition has led to suboptimal character development and weakened moral awareness among learners. Within the framework of Islamic education, guidance and counseling should serve as a space for spiritual cultivation and the development of noble character. This study aims to examine the integration of Islamic values into the guidance and counseling curriculum as a solution to the moral and identity crisis among students. The research employed a qualitative method by using a library research approach. Data were collected from academic literature, including scientific journals, books, and educational policy documents, and analyzed through stages of issue identification, thematic analysis, and conceptual synthesis. The findings indicate that Islamic values such as tawhid (monotheism), trustworthiness, patience, and sincerity can holistically strengthen GC services—both psychologically and spiritually. Implementation strategies include the development of Islamic-based counseling materials, value-based assessments, counselor training, and collaborative involvement of schools and parents. The study concludes that a contextual reform of the guidance and counseling curriculum is urgently needed to promote transformative education that fosters Islamic character in students comprehensively.